Systemic Candidiasis and TLR2 Agonist Exposure Impact the Antifungal Response of Hematopoietic Stem and Progenitor Cells - Martínez, Alba; Bono, Cristina; Megías, Javier; Yáñez, Alberto; Gozalbo, Daniel; Gil, M. Luisa (Frontiers in Cellular and Infection Microbiology, 2018)
We have previously demonstrated that Candida albicans induces differentiation of hematopoietic stem and progenitor cells (HSPCs) towards the myeloid lineage both in vitro and in vivo in a TLR2- and Dectin-1-dependent manner, giving rise to functional macrophages. In this work, we used an ex vivo model to investigate the functional consequences for macrophages derived from HSPCs in vivo-exposed to Pam3CSK4 (a TLR2 agonist) or C. albicans infection. Short in vivo treatment of mice with Pam3CSK4 results in a tolerized phenotype of ex vivo HSPC-derived macrophages, whereas an extended Pam3CSK4 treatment confers a trained phenotype. Early during candidiasis, HSPCs give rise to macrophages trained in their response to Pam3CSK4 and with an increased fungicidal activity; however, as the infection progresses to higher fungal burden, HSPC-derived macrophages become tolerized, while their fungicidal capacity is maintained. These results demonstrate that memory-like innate immune responses, already described for monocytes and macrophages, also take place in HSPCs. Interestingly, extended Pam3CSK4 treatment leads to an expansion of spleen HSPCs and myeloid cells, and strongly protects mice from systemic C. albicans infection, as the fungal burden in the kidney and spleen is drastically reduced. This protection is abrogated by immunodepletion of HSPCs, indicating their protective role against infection in this model. In addition, HSPCs produce in vitro cytokines and chemokines in response to C. albicans and Pam3CSK4, and these secretomes are capable of inducing myeloid differentiation of HSPCs and modulating peritoneal macrophage cytokine responses. Taken together, these data assign an active role for HSPCs in sensing pathogens during infection and in contributing to host protection by diverse mechanisms.